Eating location as a reference point: Differences in hedonic evaluation of dishes according to consumption situation. (December 2019) - Galiñanes Plaza, A.; Saulais, L.; Blumenthal, D.; Delarue, J.
Highlights: Restaurant setting led to higher hedonic scores regardless of the product version. The order of presentation had a greater influence than the test setting. Product labeled as "readymade" obtained lower scores than when presented in blind. Expectations associated to a given context shape consumers' evaluation of food.